Causes of casualties and the regulation of occupational health and safety in the shipping industry - Panayides, Photis; Nielsen, Detlef (My University, 2005)
The aim of this paper is to investigate maritime safety from an occupational hazards perspective as opposed to a maritime casualty perspective. It is recognised that safety in shipping should encompass casualties arising from accidents occurring in the course of performing normal seafaring duties, not just those arising from technical defects or maritime disasters. The paper discusses an investigation involving a survey of 19 flag states and two detailed studies of records kept at the Hong Kong and Singapore maritime administrations. The results indicate that occupational accidents account for a significant proportion of fatalities at sea. The statistics presented specify the ship types that are most at risk, as well as the types of occupational hazards that can most frequently lead to accidents and fatalities. The results of this study indicate voids in the process of investigating fatalities that relate to occupational accidents. These results also indicate inadequate investigation of events and causes. The creation of a database of such information could potentially be used for the development of appropriate regulations that could prevent fatal and non-fatal occupational accidents through regulatory processes. © 2005 World Maritime University.
Keywords: accident; fatalities; health and safety; ILO; IMO; occupational; seafarers